Economic empowerment pilot project in Malawi: qualitative survey report - Stefan Beierl; Francesco Burchi; Christoph Strupat (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
In order to alleviate poverty and food insecurity in Malawi – one of the poorest countries in the world – in 2016 the Government of Malawi, the Mwanza District Council, and COMSIP Cooperative Union, with the support of the GIZ Social Protection Programme, designed and implemented the Economic Empowerment Pilot Project in the district of Mwanza. The programme targets ultra-poor and labour-constrained households in six randomly selected areas of the district. Three groups of beneficiaries were identified. The first received training on group formation, financial literacy and business management, in order to increase savings and access to loans through the creation of Village Savings and Loans (VSL) groups and to improve financial and business knowledge. The second received a lump-sum transfer (about 70 USD) with the objective of raising business investments. The final group received both the lump-sum and the training. In view of the forthcoming impact evaluation, this report provides the first evidence of the immediate effects of this programme. The objective was to verify how beneficiaries spend the lump-sum transfers, in which kind of micro-business activities they engage, and what is the potential role of training (with and without lump-sum) in coming up with new business ideas and generating stable savings groups. It builds on three rounds of qualitative interviews conducted between June and October 2016. Focus group discussions with members of the VSL groups, expert interviews and interviews with purposely selected households provided further useful information. Our findings highlight the importance of providing poor households with a one-time lump-sum transfer to support their income diversification and, therefore, reduce their vulnerability. Moreover, basic financial/business training has thus far proven to be very important in ensuring that people spend the transfer in a productive way. Those who received the lump-sum transfer and training used the lump-sum significantly more for productive investments and savings (44.4% and 14.6% of the total lump-sum transfers, respectively) compared to those that only received the lump-sum transfer (36.1% and 3.3 of the total lump-sum transfers, respectively). The training has also been the key driver for the creation of VSL groups, which continue to function long after the implementation of the intervention. An increase in savings, especially combined with lump-sum transfers that increase productive investments, can smooth consumption and improve beneficiaries' living standards in the long run. Two important aspects, however, must be considered. First, in 2016, Malawi faced one of the worst droughts of the past decades, which may limit the effects of the project. Second, as most of the beneficiaries bought livestock, GIZ introduced livestock training sessions during the project because of the beneficiaries' limited knowledge about livestock rearing, feeding and health.
Keywords: 330